HUBUNGAN KUALITAS PELAYANAN DENGAN KEPUASAN NASABAH DI PT. PEGADAIAN UNIT PELAYANAN CABANG SINDANGLAUT KABUPATEN CIREBON - Gina Fatmawati; Mohammad Taufik Hidayat; Nursahidin Nursahidin (Jurnal Ilmiah Publika, 2013)
This thesis entitled "Relationship Quality Services with Customer Satisfaction in the PT.Pawnshop Branch Services Unit Sindanglaut Cirebon regency ". The problem in this study isless customer satisfaction, the problem is caused by the lack of optimal quality of service. Thepurpose of this study was to determine how the relationship of service quality with customersatisfaction at PT. Sindanglaut Pawnshop Branch Services Unit. The research hypothesis isthat the authors propose "There is a positive and significant relationship between quality ofservice and customer satisfaction in the PT. Pawnshop Branch Services Unit SindanglautCirebon regency ". Hypothesis statistics ie, Ho (null hypothesis) = rs count ≤ r ¬ s table (nopositive and significant relationship between quality of service and customer satisfaction) andHa (Alternative Hypothesis) = rs count ≥ rs table (there is a positive and significantrelationship between quality of service and customer satisfaction). The method that I use inthis paper is a survey method, survey method is research on small and large populations, butthe data is studied data from samples taken from the population, while according to the levelof explanation that the authors use in research is associative (relationship) , correlationalmethod to find the relationship between the variables x (quality of service) with variable y(customer satisfaction). Data analysis technique used is quantitative analysis (data in the formof numbers or a formula statstik as data processing), and hypothesis testing using theSpearman rank correlation coefficient formula. The population in this research were 124respondents sampling using the formula according to Burhan Bungin with precision of 10%,so the obtained samples totaling 55 respondents. Sampling techniques using simple randomsampling, simple random sampling is a technique by random sampling without regard to theexisting strata in the population is homogeneous in certain respects. Based on the resultsobtained that, the variable quality of service PT. Pawnshop Branch Services Unit Sindanglautgood enough, but not optimal. As can be seen from the success of its implementation whichachieved 58% with a total score of 3867. Customer satisfaction variables in PT. PawnshopBranch Services Unit Sindanglaut Cirebon regency was pretty good at the interval level. Thisis evident from the total score of 1951 or 59%. The relationship between quality of serviceand customer satisfaction in the PT. Pawnshop Branch Services Unit Sindanglaut CirebonDistrict is significant, because the value of rs rs count greater than 0.743 ≥ 0.265 the table.Thus, the authors propose the hypothesis thoroughly tested and accepted (Ha) and Ho(rejected).